Isolation and characterization of an avian metapneumovirus subtype C circulating in Cherry Valley ducks - Guige Xu; Bingna Wang; Zhiwen Qiao; Li Fan; Shijin Jiang; Ruihua Zhang (Poultry Science)
Since 2023, an infectious upper respiratory tract disease has been persisted in outbreaks among in a flock of Cherry Valley ducks in Shandong Province, China. This outbreak was traced to avian metapneumovirus subtype C (aMPV-C), a significant pathogen associated with egg-drop and acute respiratory diseases in poultry. It is noteworthy that prior to this, aMPV-C infection had not been previously documented in Cherry Valley ducks within China. In this study, we successfully isolated and characterized the aMPV-C LY0913 strain from the affected Cherry Valley duck flock. Sequence analysis showed that the fusion (F) protein of LY0913 exhibited a 97.8-98.7 % amino acid similarity with seven other aMPV-C strains, displaying the closest relationship to the strains isolated from Muscovy ducks in southern China in 2010. Furthermore, five concurrent amino acid mutations were identified in the F protein, providing valuable insights into the outbreak of aMPV-C in Cherry Valley ducks. The LY0913 strain demonstrated typical cytopathic effects on Vero cells and caused mortality in Cherry Valley duck embryos. In vivo infection of Cherry Valley ducklings with LY0913 reproduced the typical clinical signs and pathological lesions observed in the original infected cases. This study is the first to identify aMPV-C as a causative agent of respiratory disease in Cherry Valley ducks in China, highlighting its emergence and potential risk to previously unaffected avian populations. Urgent enhanced surveillance and biosecurity measures are strongly recommended to prevent further spread within duck flocks.